INOVASI ONE GATE SYSTEM (LONTONG BALAP) OLEH DINAS KEPENDUDUKAN PENCATATAN SIPIL DENGAN PENGADILAN NEGERI UNTUK MEWUJUDKAN PERUBAHAN DOKUMEN ADMINISTRASI KEPENDUDUKAN KOTA SURABAYA - Diputra, Dicky Lintang; Megawati, Suci (Universitas Negeri Surabaya, 2024)
Program innovation is an effort to meet the needs of the community in accessing public services. In particular, the public services needed by the community are public services in the field of population administration, so that city and district governments continue to be encouraged to innovate. One of the program innovations that has been launched by the Surabaya City Government is the Lontong Balap program innovation. However, in carrying out the Lontong Balap program, problems were still encountered during its implementation. The purpose of this research is to examine further the implementation of the Lontong Balap Innovation Program. The type of research carried out was descriptive-qualitative. This research uses six indicators that influence the success of policy implementation according to Van Meter and Van Horn (1975), including policy standards and targets, resources, characteristics of implementing agents, inter-organizational relationships, dispositions, and economic, social, and political conditions. The methods used in collecting data are interviews, observation, and documentation. Then it is analyzed through several stages, such as data collection, data reduction, data presentation, and drawing conclusions. The research results show that the implementation of the Lontong Balap program is good but still not optimal. Such as human resources such as trial judges, verifiers, registration, and making determinations. The provision for sub-district employees often causes input errors, monitoring and evaluation processes in each sub-district are not running well, and the socialization process that has been carried out has not reached all levels of Surabaya city society.